Innovation and entrepreneuship networks as global competitiveness drivers - Farinha, Luís Manuel do Carmo (2017)
The main aim of this thesis is to analyze the relationship between innovation, entrepreneurship and competitiveness, following the triple helix network approach to regional economies, considering their impact on socio-economic development. This correspondingly involved a mixed research typology, as advocated in chapters 2 to 5, alternating between quantitative methodologies, deploying descriptive statistics, structural equation modelling (SEM) and hierarchical cluster analysis; and the qualitative methodology underpinning the case studies. The socio-economic prosperity of triple helix spaces (Academia-Industry-Political Decision regional spaces of interaction) depends on competitive advantages, including their positioning in terms of innovation and entrepreneurship factors, local endogenous resources and the development trajectories attained. The study revealed the scope for grouping the countries analyzed by the Global Competitiveness Report (GCR) and the Global Entrepreneurship Monitor (GEM) into five clusters: (1) Balanced low performance, (2) Moderate competitiveness, (3) High competitiveness, (4) High GDP per capita, and (5) Performance excellence. Making direct comparisons between European regions, and with reference to the recognized United Kingdom centre of entrepreneurship in Oxfordshire, we recommend some future paths for the Centro region of Portugal, strongly based on the opportunities arising out of the Horizon 2020 programme and RIS3. Our conclusions point to the sheer relevance of important contributions from the regional and technological clusters and the collaborative A-I research and development projects studied to the overall socio-economic development of economies. In summary, we may highlight two important theoretical contributions from this thesis: (1) the presentation of the "Regional Helix Turbine Model", clarifying the role of different actors within the context of triple helix regional spaces and their potential contribution to enhancing competitiveness; and (2) the definition of a performance measurement model appropriately adjusted to these dynamics: the "Helix Regional Scoreboard". As recommendations and future lines of research, we would call for the completion of comparative studies on the trajectories of triple helix regional spaces across Europe featuring different levels of innovation and competitiveness as well as the "RHS" validation through the comparison of the Oxfordshire and Centro regions,, both included in this thesis.